Magic, Idleness and Comedy: Late Agamben’s Marxist Reaction to Neoliberal Political Theology - Ronel, Yoav (Political theology, 2024)
This article deals with Giorgio Agamben's late work, arguing that Agamben’s trans secular critique of capitalist political theology is incepted from the historical conditions of late neoliberalism – with its focus on the personal “self” as its anchor. It suggests that to understand Agamben’s trans secular reaction to late neoliberalism we need historicized his thought. As historicized, it can reveal the dialectical limits of neoliberalism. To do so, the article reads late Agamben texts next to contemporary Marxist thinkers Alenka Zupančič and her theory of comedy, Todd McGowan and his analysis of Capitalism and desire and Sianne Ngai and her conceptualization of zaniness as the aesthetic representation of neoliberal precariousness. Moving on, the article focuses on Agamben’s late book Pulcinella. It argues that the book not only expresses the limits of neoliberalism but also uncovers hope and promises for comic theological renewal beyond neoliberalism and its cult of the self.